ANALYSIS OF BPJS PATIENT SATISFACTION WITH THE QUALITY OF HEALTH SERVICES IN 2024 - Handayani, Tri; Chairil Zaman; Dianita Ekawati (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Satisfaction is a response received, then compared with performance according to expectations. The performance of the health services received exceeds expectations, so the patient feels satisfied, conversely, if the performance they receive does not meet their expectations, it can be said that the consumer feels dissatisfied. This study aims to determine factors related to BPJS patient satisfaction with the quality of health services at the Muara Kulam Community Health Center in 2024. The design of this research is quantitative with a cross-sectional approach.  The population of this study was BPJS patients who received treatment at the Muara Kulam Community Health Center in 2023, totaling 717 respondents. The sample in this study amounted to 88 people. The sampling method uses purposive sampling using the Slovin formula.  Inclusion criteria are willing to be a respondent by filling out a consent form. This research was carried out on March 28 - April 28 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test. The research results show a  tangibles (p value 0.005), responsiveness (p value 0.006) and empathy (p value 0.05) with BPJS patient satisfaction at the Muara Kulam Community Health Center in 2024. Conclusion: there is a relationship between tangibles, responsiveness and empathy with BPJS patient satisfaction in Muara Kulam Community Health Center in 2024. The Community Health Center should complete the facilities and infrastructure at the Community Health Center such as examination equipment